2021
DOI: 10.3390/rs13040728
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Interannual Variability of Sea Surface Salinity Near Major River Mouths of the World Ocean Inferred from Gridded Satellite and In-Situ Salinity Products

Abstract: Large rivers are key components of the land-ocean branch of the global water and biogeochemical cycles. River discharges can have important influences on physical, biological, optical, and chemical processes in coastal oceans. It is, therefore, of importance to routinely monitor the time-varying dispersal patterns of river plumes. The European Space Agency (ESA) Soil Moisture and Ocean Salinity (SMOS) and the NASA Soil Moisture Active Passive (SMAP) satellites provide Sea Surface Salinity (SSS) observations ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
(32 reference statements)
3
20
0
Order By: Relevance
“…This further underscores the values of satellite data in monitoring winter and spring conditions in the future. In addition, a previous study has demonstrated that remote sensing salinity can reflect the SSS variability near major rivers in lower and middle latitudes [51]. Our assessment of satellite products near the Yukon River further confirms its robustness and benefits in understanding the intense salinity changes near such a high-latitude river.…”
Section: Discussionsupporting
confidence: 78%
“…This further underscores the values of satellite data in monitoring winter and spring conditions in the future. In addition, a previous study has demonstrated that remote sensing salinity can reflect the SSS variability near major rivers in lower and middle latitudes [51]. Our assessment of satellite products near the Yukon River further confirms its robustness and benefits in understanding the intense salinity changes near such a high-latitude river.…”
Section: Discussionsupporting
confidence: 78%
“…This localized freshening is dictated by the hydrological forcing through local rainfall and river discharges (Gierach et al, 2013;Grodsky et al, 2014;Chao et al, 2015;da Silva & Castelao, 2018;Fournier, Vandemark, et al, 2017;Fournier, Vialard, et al, 2017). In general, plume features are underestimated in in situ products (Fournier & Lee, 2021).…”
Section: The 3-year Mean Sss Fieldsmentioning
confidence: 99%
“…This can be attributed to river discharges as illustrated here in the Amazon River plume and the Bay of Bengal regions (Figures 6 and 8) and previously documented in regional studies [15,46,47,69,[94][95][96]. More recently, SMOS and SMAP have been shown to reproduce well seasonal and interannual SSS variation in the mouths of major rivers [97]. Strong coastal precipitations in the tropics could also induce such freshening [13,45] but their potential contribution could not be quantified here.…”
Section: Discussionmentioning
confidence: 69%